Endometrial study by Ultrasonography and its correlation with Histopathology in Abnormal uterine bleeding - Shrestha, Pravin; Shrestha, Smita; Mahato, Vibha (Asian Journal of Medical Sciences, 2018)
Background: Abnormal Uterine Bleeding is defined as any deviation from a normal menstrual pattern. It is one of the common presentation in extremes of ages. However endometrial hyperplasia and carcinoma are commoner in perimenopausal and postmenopausal women warranting investigations like ultrasonography and endometrial biopsy. Aims and Objective: The aim of the study was to note the endometrial thickness by transabdominal ultrasonography and observe the histopathological pattern in women presenting with abnormal Uterine Bleeding. Material and Methods: Premenopausal women more than 45 years of age and the postmenopausal patients, without any pelvic pathology were included in the study. Endometrial thickness was measured by transabdominal sonography and endometrial biopsy was done. Tissue obtained was sent for histopathological examination. Results: A total of 105 patients were studied. Majority (92%) of patients were premenopausal. Proliferative Endometrium (32%) was the most common finding in premenopausal and atrophic endometrium (37.5%) in postmenopausal group. Malignancy was higher in a postmenopausal group (12.5%) as compared to the premenopausal group (2%). Malignancy was not seen when endometrial thickness was less than 11mm in the premenopausal age group. Endometrial hyperplasia was also more common when the thickness was more than 11mm.In postmenopausal group12.5% of patients, had complex hyperplasia.25% had simple hyperplasia and malignancy was seen in 12.5% of patients. When endometrial thickness was less than 5 mm, hyperplasia and malignancy was not seen. Conclusion: Measurement of Endometrial thickness and histopathological workup in patients above 45 years presenting with abnormal uterine bleeding will be helpful in detecting endometrial hyperplasia and carcinoma. Asian Journal of Medical Sciences Vol.9(2) 2018 31-35